1982
DOI: 10.1271/bbb1961.46.2441
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the state of aromatic amino acid residues in heated soybean 7S globulin by absorption derivative spectrophotometry and spectrofluorimetry.

Abstract: The heating of 7S globulin caused changes in the intensities, but hardly affected the positions of the peaks and troughs of the second derivative absorption spectra at wavelengths below 270 nm. On the other hand, above 271 nm, changes were reflected both in the intensities and in the positions of peaks and troughs. The difference-second derivative absorption spectra indicated that 60 and 70 percent, respectively, of phenylalanine and tyrosine residues buried in the native 7S globulin remained as the buried for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These results gave information about the state of aromatic residues in the proteins. Peaks between 250 and 270 nm are due to phenylalanine, while those between 270 and 300 nm are contributed predominately by the tyrosine and tryptophan residues (Yamagishi et al . 1982, 1983; Ma and Harwalkar 1988; Klepacka et al .…”
Section: Resultsmentioning
confidence: 99%
“…These results gave information about the state of aromatic residues in the proteins. Peaks between 250 and 270 nm are due to phenylalanine, while those between 270 and 300 nm are contributed predominately by the tyrosine and tryptophan residues (Yamagishi et al . 1982, 1983; Ma and Harwalkar 1988; Klepacka et al .…”
Section: Resultsmentioning
confidence: 99%
“…A broader shoulder or different relative ratios between peaks can represent these differences. Some researchers have reported on the use of fluorescence as an analytical tool for monitoring globulin proteins (Nakhost & Karel, 1983), amino acid residues (Yamagishi et al. , 1982), protein modification for various grain proteins (Kim & Rhee, 1989; Deshpande & Damodaran, 1990) and other physico‐chemical parameters (Sharma & Schulman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These sales are expected to increase following the FDA ruling that has approved the use of the health claim that soybean intake could lower blood cholesterol and reduce the risk of heart disease if consumed as part of low fat diet (Stein, 2000). Two of the reasons behind the increased consumption are the low soybean price and the tremendous amount of research that has been done on soybean to improve its functionality (Yamagishi et al. , 1982; Kim & Rhee, 1989; Wagner et al.…”
Section: Introductionmentioning
confidence: 99%
“…These authors measured an increase in hardness in 7S protein after heating and cooling. Measuring aromatic amino acids in 7S soy protein, Yamagishi et al (1982) found few alterations in the quaternary structure after heating at 100°C. Phenylalanine residues were slightly more exposed, but not as much as when hydrogen bonds were disrupted.…”
Section: Soy Protein Functionalitymentioning
confidence: 99%